1997
DOI: 10.1086/313053
|View full text |Cite
|
Sign up to set email alerts
|

ASCAObservations of Type 2 Seyfert Galaxies. I. Data Analysis Results

Abstract: We present ASCA spatial, temporal, and spectral data for a sample of 26 observations of 25 type 2 active galactic nuclei (AGNs), composed of 17 Seyfert 2 galaxies and eight narrow emission line galaxies (NELGs). Twenty-four of the 25 sources were detected.The ASCA images are generally consistent with emission from point sources at energies above D3 keV. We use archival ROSAT data to examine each Ðeld at high spatial resolution and to check for the presence of sources that would contaminate the ASCA data.Of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
297
5
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 305 publications
(341 citation statements)
references
References 95 publications
37
297
5
2
Order By: Relevance
“…The investigation on the true nature of this soft X-ray component will be the subject of the next sections. Here it is important to note that whatever the fitting of the data below ∼1 keV, the best-fit model for the nuclear emission of NGC 5252 above ∼1 keV is typical in shape, but flatter (Γ ∼ 1.4-1.5) than normally found from Seyfert 2 galaxies (Γ = 1.5-2.5, Turner & Pounds 1989;Turner et al 1997; Cappi et al 2006;Dadina 2008). It is however consistent with the previous ASCA measurement (Γ ∼ 1-1.5, Cappi et al 1996), confirming the need in this source for a more complex absorption (either multiple, ionised or both) to recover a steeper canonical photon index.…”
Section: The Nuclear Spectrummentioning
confidence: 84%
See 1 more Smart Citation
“…The investigation on the true nature of this soft X-ray component will be the subject of the next sections. Here it is important to note that whatever the fitting of the data below ∼1 keV, the best-fit model for the nuclear emission of NGC 5252 above ∼1 keV is typical in shape, but flatter (Γ ∼ 1.4-1.5) than normally found from Seyfert 2 galaxies (Γ = 1.5-2.5, Turner & Pounds 1989;Turner et al 1997; Cappi et al 2006;Dadina 2008). It is however consistent with the previous ASCA measurement (Γ ∼ 1-1.5, Cappi et al 1996), confirming the need in this source for a more complex absorption (either multiple, ionised or both) to recover a steeper canonical photon index.…”
Section: The Nuclear Spectrummentioning
confidence: 84%
“…It has been well known since the early days of X-ray spectroscopy that excess emission above the extrapolation of the absorbed nuclear radiation is present in almost all bright Seyfert 2s (Turner et al 1997). This excess appears smooth when measured with instruments with moderate energy resolutions like CCD.…”
Section: Introductionmentioning
confidence: 99%
“…Under the simple picture of a static dusty torus around an AGN, both optical and X-ray measurements of the gas column density should agree. To a large extent this is true, as many studies find that Type 1 AGNs show little to no X-ray absorption, while most Type 2 AGNs are X-ray absorbed with N H 10 22 cm −2 (e.g., Smith & Done 1996;Turner et al 1997;Risaliti et al 1999;Garcet et al 2007;Mainieri et al 2007;Tajer et al 2007;Antonucci 2012;Malizia et al 2012;Merloni et al 2014;Davies et al 2015) in accordance with the unified model. Of course, the unified model, while broadly successful in explaining the diversity of AGNs, is simplified and investigations of differences between Type 1 and Type 2 AGNs that cannot be explained by this paradigm can help to reveal the complex nature of AGNs.…”
Section: Introductionmentioning
confidence: 88%
“…However, often the observed profiles do not match the theoretical calculations (Fabian et al 1989;Laor 1991;Matt et al 1992). Electron scattering, as often observed in type 2 Seyferts (Ueno et al 1994;Turner et al 1997;Matt et al 2000), may help reconciling the difference between observed and theoretical line profiles produced in X-ray illuminated, relativistic accretion disks Matt et al 2001). Other pieces of evidence suggest constraints on the nature of the accretion: the disk may be truncated at a radius where relativistically broadened wings are negligible (see, Send offprint requests to: M. Guainazzi, e-mail: mguainaz@xmm.vilspa.esa.es e.g.…”
Section: Introductionmentioning
confidence: 92%